Penerapan Metode Project Based Learning (PjBL) dalam Meningkatkan Hasil Belajar pada Mata Pelajaran IPA di SDN Sukabumi Selatan 06 Pagi - Zayda, Nada Khadi (Lembaga Yasin AlSys, 2023)
This research is motivated by observational data which shows that the acquisition of student learning outcomes in science material is very low. To respond to this, researchers conducted research aimed at improving student learning outcomes. The objectives to be achieved in this study include: (1) To describe the application of the Project Based Learning method at SDN Sukabumi Selatan 06 Pagi, (2) To describe the problems encountered in implementing the Project Based Learning method at SDN Sukabumi Selatan 06 Pagi, (3) ) To describe science learning outcomes by applying the project based learning method at SDN Sukabumi Selatan 06 Pagi. This study used a qualitative method and was conducted in grade 6 with a total of 32 students. The results of the study showed an increase in learning outcomes. With the project based learning method students can improve their learning outcomes.